The improved piezoelectric properties of ZnO nanorods with oxygen plasma treatment on the single layer graphene coated polymer substrate. Issue 2 (10th January 2014) - Hussain, Mushtaque; Abbasi, Mazhar Ali; Ibupoto, Zafar Hussain; Nur, Omer; Willander, Magnus
<x xml:space="preserve">Abstract</x> The step towards the fabrication of nanodevices with improved performance is of high demand; therefore, in this study, oxygen plasma treated ZnO nanorods based piezoelectric nanogenerator is developed on the single layer graphene coated PET flexible polymer substrate. ZnO nanorods on the single layer graphene are grown by hydrothermal growth method and the structural study is carried out by using X‐ray diffraction (XRD), scanning electron microscopy (SEM), and transmission electron microscopy (TEM). The piezoelectric properties of ZnO nanorods with and without plasma treatment were investigated by atomic force microscopy (AFM). The oxygen plasma treated sample of ZnO nanorods showed significant increase in the piezoelectric potential which could be due to the decrease in the defects levels in the ZnO and also increase in the mechanical properties of ZnO nanorods. Furthermore X‐ray photoelectron spectroscopy (XPS) confirms that the filling of vacancies by oxygen in the matrix of ZnO using oxygen plasma treatment has gave an enhanced piezoelectric potential compared to the sample of ZnO nanorods not treated with oxygen plasma. In addition to XPS experiment, cathodoluminescence (CL) technique was used for the determination of defect level in the ZnO nanorods after the treatment of oxygen plasma and the obtained information supported the XPS data of oxygen plasma treatment sample by showing the decreased level of defect levels in the prepared sample. From the XPS and CL studies, it is observed that the defect level has significant influence on the piezoelectric potential of the ZnO nanostructures.